2008
DOI: 10.1590/s0100-39842008000300006
|View full text |Cite
|
Sign up to set email alerts
|

Correlação entre o achado ultra-sonográfico isolado de cisto de cordão umbilical e anomalias fetais

Abstract: OBJECTIVE: To correlate the isolated sonographic finding of umbilical cord cyst with fetal anomalies such as chromosomopathies and structural changes. According to the medical literature, the clinical implications of the sonographic finding of umbilical cord cyst in the second and third trimesters of pregnancy are well established; however, the meaning of this finding in the first trimester still remains controversial. MATERIALS AND METHODS: A retrospective study was developed with consecutive, pregnant women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…11,14 Isolated UC cysts, as seen in this case, are considered to have a favorable fetal outcome. Kobayashi et al, 15 in their study, evaluated nine fetuses who presented with isolated UC cysts at birth and all of them had an uneventful birth and normal development. Similarly, Zangen et al 4 reported isolated UC cysts with an uneventful fetal outcome in 7 of the 10 cases evaluated by them.…”
Section: Discussionmentioning
confidence: 99%
“…11,14 Isolated UC cysts, as seen in this case, are considered to have a favorable fetal outcome. Kobayashi et al, 15 in their study, evaluated nine fetuses who presented with isolated UC cysts at birth and all of them had an uneventful birth and normal development. Similarly, Zangen et al 4 reported isolated UC cysts with an uneventful fetal outcome in 7 of the 10 cases evaluated by them.…”
Section: Discussionmentioning
confidence: 99%